AUTHORS’ PATRIOTISM ON THE BALKANS - Ana Ashtalkovska Gajtanoska (EtnoAntropoZum, 2021)
The concept according to which the scientists from certain social sciences and humanities have the duty to work in favor of nourishing, strengthening, and glorifying one's national identity is risky on many grounds. Although there are certain positive changes with new generations of scientists when it comes to this issue, still it can be stated that in a wider public discourse the romantic idea is very much alive - about the ethnologists or the historians who should (or must) be patriots. The position of “professional patriots[1]” is analyzed from a theoretical and methodological point of view, illustrated by examples from Macedonian ethnology and its relation to “historical truths” in a contemporary context. Urgent paradigm reforms are much needed in order for social sciences and humanities to become a factor of integration instead of a factor of disintegration on the Balkans.